2016
DOI: 10.1039/c6ra06438h
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of carboxymethyl cellulose sodium/graphene oxide hydrogel microparticles for water purification

Abstract: Carboxymethyl cellulose sodium (CMCNa)/graphene oxide (GO) hydrogel microparticles (CGs) with the diameter of 2.2–3.6 μm were prepared facilely via spray drying and used as adsorbents for water purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…16g–i ). The {002} planes of graphene with a lattice spacing of 0.32 nm 41 44 are also seen in HRTEM of the graphenic carbon fragments formed on Ag NPs by irradiation in C 2 H 4 (Fig. 3e ).…”
Section: Resultsmentioning
confidence: 77%
“…16g–i ). The {002} planes of graphene with a lattice spacing of 0.32 nm 41 44 are also seen in HRTEM of the graphenic carbon fragments formed on Ag NPs by irradiation in C 2 H 4 (Fig. 3e ).…”
Section: Resultsmentioning
confidence: 77%
“…The stretching vibration of O−H blue shifts to 3433 cm −1 , which indicates the formation of the composite is facilitated by H-bonding interaction between CGO and CMC. On the other hand, the carbonyl stretch of carboxylate groups of CMC was overlapped with that of carboxylic groups of CGO at about 1577 cm −1 , which is attributable to the interaction between the hydroxyl groups of CMC and the carboxyl groups of CGO [ 44 , 53 ]. In addition, it is worthwhile mentioning that the new peak at 1654 cm −1 is assigned to −NH(R) functional groups [ 54 ], suggesting that EDA produced a covalent bond during cross-linking with CGO, in consistent with the Raman analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang Y. et al prepared CMC/GO monoliths (GO, 0.2~5.0 wt %) by a unidi-rectional freeze-drying method, and proved that the adsorption efficiency of multiple heavy metal ions was improved [ 43 ]. Liu J. et al fabricated CMC/GO hydrogel microparticles (GO, 2~8 wt %) via spray drying, and found that these hydrogel microparticles can effectively improve the adsorption capacity of dye molecules (59 mg·g −1 for methylene blue and 66 mg·g −1 for Eosin Y) [ 44 ]. Varaprasad K. et al conducted preparation on dye removal CMC-Acrylamide-GO hydrogels (GO, 0.05~0.14 wt %) by a free-radical polymerization method; the resulting maximum acid blue absorption capacity was 185.45 mg·g −1 [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CMCNa presents characteristic peaks at 1595 cm -1 (stretching vibration of carboxylate group), 3402 cm -1 (O-H stretching vibration), 2912 cm -1 (C-H stretching vibration), 1421 cm -1 (-CH2 scissoring vibration), 1322 cm -1 (-OH bending vibration), 1060 cm -1 , (>CH-O-CH2 stretching vibrations), respectively (Liu et al, 2016). The structure of CollCMCNa presented many changes compared with control one (Coll -AX 3.1.)…”
Section: Resultsmentioning
confidence: 99%